2016
DOI: 10.1093/jjco/hyw175
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of eribulin in patients with previously treated advanced or metastatic soft tissue sarcoma†

Abstract: This phase 2 study investigated eribulin in previously treated Japanese patients with advanced/metastatic soft tissue sarcoma. Eribulin showed clinical activity together with a manageable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 21 publications
4
56
6
Order By: Relevance
“…Another open-label, multicentre, and non-randomized Phase II trial evaluated patients with advanced or metastatic STS. This study found a median PFS and ORR for LPS/LMS patients of 5.5 and 17.0 months, respectively, against 2.0 months for both parameters in other subtypes (Kawai et al, 2017…”
Section: Clinical Evidencesmentioning
confidence: 54%
“…Another open-label, multicentre, and non-randomized Phase II trial evaluated patients with advanced or metastatic STS. This study found a median PFS and ORR for LPS/LMS patients of 5.5 and 17.0 months, respectively, against 2.0 months for both parameters in other subtypes (Kawai et al, 2017…”
Section: Clinical Evidencesmentioning
confidence: 54%
“…More recently, clinical trials of eribulin for the treatment of soft‐tissue sarcoma have been reported . According to those clinical trials, eribulin was permitted for the treatment of soft‐tissue sarcoma, but not angiosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…It may be used as therapy for metastatic breast cancer or metastatic/unresectable liposarcomas. A phase II study of eribulin in patients with previously treated late-stage or metastatic soft tissue sarcoma found pancyptopaenia and febrile neutropaenia to be the most common adverse effects 19. Additional side effects of eribulin include fatigue, alopecia, gastrointestinal manifestations, peripheral neuropathy and QT prolongation.…”
Section: Discussionmentioning
confidence: 99%